PROSPECTIVE TEACHERS' PERCEPTIONS OF ENGLISH AREA TRAINING: ENHANCING 21ST-CENTURY COMPETENCIES - Hustiana Hustiana; Dwi Adi Nugroho; Asdar Asdar; Nurqadriyanti Hasanuddin; Ahmad Junaedi; Fajriani Fajriani (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2025)
This study explored the perceptions of prospective teachers regarding the English Area Training at SMA 3 Majene in Sulawesi Barat and its influence on the enhancement of their competencies pertinent to the 21st century: communication, collaboration, creativity, and critical thinking, essential for future teachers' professional growth. The data sources were four prospective teachers selected through purposive sampling. They held a bachelor's degree for at least five months and had not become civil servant teachers or participated in Teacher Professional Education (PPG). Participants emphasized the significance of English Area Training in developing their 21st-century competencies. The research results indicated that prospective teachers generally have positive views on their communication skills, noting improvements through practice and feedback. In terms of collaboration, while three teachers felt the English area enhancement fostered cooperation, one disagreed with this strategy. Prospective teachers also reported increased creativity through innovative methods like games, which engage students. They experienced enhanced critical thinking through discussions and problem-solving together. The study suggests future researchers focus on the English area theme by integrating technology with effective methods to better engage Generation Z.